Travis - Sheridan, Mia (Naperville, Illinois : Bloom Books, 2023)
Travis Hale is the police chief in idyllic Pelion, Maine. His past is riddled with regrets, but his future looks limitless, women are regularly falling at his feet, and his family has mostly forgiven his mistakes. But when the new guy in town crosses him, things start to look shaky--especially when he meets the stranger's smoothie-making, birdseed-eating sister. Haven Torres's life fell apart. Or, rather, burned to the ground. At the time, it seemed like a solid idea to jump in her car, her brother a mostly-willing co-pilot, and embark on a cross-country adventure for the summer. Especially if she can catch the attention of Pelion's most eligible bachelor, Gage Buchanan, before she goes. And after the local police chief tells her of her brother's scandalous misdeed, she knows without a doubt that Pelion is just another town where their stay is best short-lived.
Keywords: Man-woman relationships -- Fiction; Police chiefs -- Fiction; Maine -- Fiction; Romance fiction; Novels